2017
DOI: 10.7155/jgaa.00438
|View full text |Cite
|
Sign up to set email alerts
|

Progress on Partial Edge Drawings

Abstract: Recently, a new way of avoiding crossings in straight-line drawings of non-planar graphs has been introduced. The idea of partial edge drawings (PED) is to drop the middle part of edges and rely on the remaining edge parts called stubs. We focus on symmetric partial edge drawings (SPEDs) that require the two stubs of an edge to be of equal length. In this way, the stub at the other endpoint of an edge assures the viewer of the edge's existence. We also consider an additional homogeneity const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…We extended the work by Bruckdorfer et al [6] and showed NP-hardness for the MaxPED and MaxSPED problems, as well as polynomial-time algorithms for the case of the intersection graph of the input drawing being a tree or having bounded treewidth. For the latter, our proof-of-concept implementation worked reasonably well for small to medium-size instances.…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…We extended the work by Bruckdorfer et al [6] and showed NP-hardness for the MaxPED and MaxSPED problems, as well as polynomial-time algorithms for the case of the intersection graph of the input drawing being a tree or having bounded treewidth. For the latter, our proof-of-concept implementation worked reasonably well for small to medium-size instances.…”
Section: Resultsmentioning
confidence: 72%
“…As a first result, Bruckdorfer and Kaufmann [7] presented an integer linear program for solving MaxSPED on general input drawings. Later, Bruckdorfer et al [6] gave an O(n log n)-time algorithm for MaxSPED on the class of 2-plane input drawings (no edge has more than two crossings), where n is the number of vertices. They also described an efficient 2-approximation algorithm for the dual problem of minimizing the amount of erased ink for arbitrary input drawings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The layout of a graph G is the positioning of the given vertices V to n (normally) distinct locations in the display space, whereas the edges in between are drawn as either straight, curved, orthogonal [ 29 ], or partial links [ 30 , 31 ], depending on several esthetic graph drawing criteria to be followed [ 32 ].…”
Section: Data and Visualizationsmentioning
confidence: 99%
“…Although we decide to use the node-link visual metaphor in this work, we argue that additional enhancements to the link representation can become a powerful concept to represent long graph sequences. In this article, we argue that we do not need the complete link in a node-link diagram to show connectedness of objects as evaluated by Burch et al, 12 invented by Becker et al, 24 and mathematically modeled as partial edge drawing by Bruckdorfer et al 25 Although there are many other link representation styles like curved, orthogonal, or tapered ones which are evaluated by Holten and Van Wijk, 26 we use traditional straight link drawings with equally thick lines. But, as an enhancement to the parallel edge splatting concept introduced by Burch et al, 11 we focus on space-efficiency aspects.…”
Section: Related Workmentioning
confidence: 99%